2021
DOI: 10.46291/ispecjasvol5iss4pp766-772
|View full text |Cite
|
Sign up to set email alerts
|

Households’ Perception of Fruits and Vegetables Consumption in Olorunda Local Government Area, Osun State, Nigeria

Abstract: This study assessed respondents’ perception of fruits and vegetables consumption in the study area. Relevant data were collected from one hundred and twenty (120) randomly sampled households. Data were analyzed as appropriate. Results showed that 68.3% of the respondents were females, 96.7% had varying degrees of formal education while means of household size and monthly income were 4±2 persons and ₦57,500±23,300, respectively. Respondents had strong perception for the facts that vegetables can be easily incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…For instance; Kitinoja et al [15] posited that losses of highly perishable leafy vegetables have been measured to be as high as 70-80% in West Africa including Nigeria. Idris-Adeniyi et al [16] reported that marketers in Nigeria suffer a lot because of the marketing techniques they employ which are resulted in high postharvest losses of up to 70% while other African countries experienced postharvest losses as high as above 50%. Gebru and Belew [13] have also reported postharvest loss of fruits and vegetables in other parts of the world as; Europe and Russia (56%), North America & Oceania (66%), Industrialized Asia (43%), Sub-Saharan Africa (66%), Latin America (72%), United States (31%) and Ethiopia (50%).…”
Section: Introductionmentioning
confidence: 99%
“…For instance; Kitinoja et al [15] posited that losses of highly perishable leafy vegetables have been measured to be as high as 70-80% in West Africa including Nigeria. Idris-Adeniyi et al [16] reported that marketers in Nigeria suffer a lot because of the marketing techniques they employ which are resulted in high postharvest losses of up to 70% while other African countries experienced postharvest losses as high as above 50%. Gebru and Belew [13] have also reported postharvest loss of fruits and vegetables in other parts of the world as; Europe and Russia (56%), North America & Oceania (66%), Industrialized Asia (43%), Sub-Saharan Africa (66%), Latin America (72%), United States (31%) and Ethiopia (50%).…”
Section: Introductionmentioning
confidence: 99%